2009
DOI: 10.3390/molecules14082947
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of Some Plant Extracts Towards Xanthine Oxidase, Lipoxygenase and Tyrosinase

Abstract: Natural products have the potential to be developed into new drugs for the treatment of various diseases. The aim of the present study was to screen the antioxidant activities of some common edible fruits, garden plants and medicinal plants indigenous to Taiwan. This was performed by assessing the activities of lipoxygenase, xanthine oxidase and tyrosinase following incubation with extracts from these plants. A further aim was to use HPLC-DAD and tyrosinase to chromatographically identify the antioxidative con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(69 citation statements)
references
References 23 publications
5
56
1
1
Order By: Relevance
“…The acetone extract of A.bettzickiana has been recorded to possess lipoxygenase, tyrosinase and xanthine oxidase inhibitory activities 15 . Consequently, the fresh flowers of A.bettzickiana ( Fig.…”
Section: Determination Of In Vitro Antioxidant Capacitymentioning
confidence: 99%
See 2 more Smart Citations
“…The acetone extract of A.bettzickiana has been recorded to possess lipoxygenase, tyrosinase and xanthine oxidase inhibitory activities 15 . Consequently, the fresh flowers of A.bettzickiana ( Fig.…”
Section: Determination Of In Vitro Antioxidant Capacitymentioning
confidence: 99%
“…3 and 4), that have been identified from the lipophilic fraction are tabulated (Table 2). Eighteen saturated [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] and four unsaturated [19][20][21][22] hydrocarbons, ten saturated [23][24][25][26][27][28][29][30][31][32] cholesterol homologues and it is reported that lowdoses of phytosterol-supplementation has produced significantly lowered plasma total cholesterol 22 . Such lipid-lowering effect of phytosterols is claimed to be mediated by competitive inhibition of cholesterol absorption and by transcriptional induction of genes implicated in cholesterol metabolism in both enterocytes and hepatocytes.…”
Section: Separation and Identification Of The Lipophilic Metabolitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Rhodiola rosea extracts was studied as melanogenesis suppressor. The acetone extract of R. rosea exhibits tyrosinase inhibitory activity [48]. Besides R. rosea root containing phenylethanol derivatives, phenylpropanoids, monoterpenes, flavonoids, phenolic acids, and triterpenes [49,50] decreases melanin content in B16 melanoma cells via suppressing the expressions of MC1R, a receptor of a-MSH, MITF, TRP-1, and tyrosianse [51].…”
Section: Regulator On Expression Of Melanogenic Enzymesmentioning
confidence: 99%
“…Oxidative stress takes place in the human body when there is an upsurge in the amount of free radicals, or reactive oxygen species (ROS) that cannot be contained by our body's antioxidant defense system, therefore, leading to harmful diseases (Chin et al 2009). Normally, the human body has the ability to scavenge ROS using its naturally occurring antioxidant defense system and there is equilibrium between the ROS formation and dissipation.…”
Section: Introductionmentioning
confidence: 99%